Requirements for market entry of gene drive-modified mosquitoes for control of vector-borne diseases: analogies to other biologic and biotechnology products - James, Stephanie L.; Quemada, Hector; Benedict, Mark Q.; Dass, Brinda (Frontiers in Bioengineering and Biotechnology, 2023)
Gene drive-modified mosquitoes (GDMMs) are proposed as new tools for control and elimination of malaria and other mosquito-borne diseases, and promising results have been observed from testing conducted in containment. Although still at an early stage of development, it is important to begin now to consider approval procedures and market entry strategies for the eventual implementation of GDMMs in the context of disease control programs, as these could impact future research plans. It is expected that, as for other types of new products, those seeking to bring GDMMs to market will be required to provide sufficient information to allow the regulator(s) to determine whether the product is safe and effective for its proposed use. There already has been much emphasis on developing requirements for the biosafety components of the "safe and effective" benchmark, largely concerned with their regulation as genetically modified organisms. Other potential approval requirements have received little attention, however. Although GDMMs are expected to be implemented primarily in the context of public health programs, any regulatory analogies to other public health products, such as pharmaceuticals, vaccines, or chemical pesticides, must take into account the characteristics of live mosquito products. Typical manufacturing standards related to product identity, potency or quality will need to be adapted to GDMMs. Valuable lessons can be drawn from the regulatory approval processes for other whole organism and genetically modified (GM) organism products. Supply chain requirements, such as scale of production, location and design of production facilities, and methods of distribution and delivery, will be dependent upon the characteristics of the particular GDMM product, the conditions of use, and the region to be served. Plans for fulfilling supply chain needs can build upon experience in the development of other live insect products for use in public health and agriculture. Implementation of GDMMs would benefit from additional research on enabling technologies for long-term storage of mosquito life stages, efficient mass production, and area-wide delivery of GDMMs. Early consideration of these practical requirements for market entry will help to mitigate downstream delays in the development of these promising new technologies.